Development Reading Assessment Media to Understanding Javanese Language Computer Based on Test for Students on Javanese Language and Literature Department - Irkhamudin, Irkhamudin; Supriyanto, Teguh (Pascasarjana Universitas Negeri Semarang, 2018)
The need for reading comprehension assessment tools that can measure the ability of Javanese in Javanese Language and Literature students is the background of this research. The purpose of this study was to develop a medium for assessing reading comprehension using computer digital media. The product developed in this study is in the form of an evaluation application in the form of a flash, which created with a Quiz Creator application that can also be used by other researchers to make an evaluation or test questions. This evaluation media development model uses the ADDIE model (analysis, design, development, implementation, evaluation) developed by Dick, and Carey (2001). The result is the students are more interested in using media assessment in reading the Computer Based Test understanding because it is easy to use, a good look and a modern digital concept. The assessment score and the category of student achievement in reading comprehension skills can be immediately known. The hopefully, the developing assessment media reading this understanding, inspires to build another evaluation media with modern digital concepts, so that learning and evaluation are not considered boring for educators and students.